PMO-078 Technical feasibility: mechanically-retained low-profile button gastrostomy. (28th May 2012) - Cain, J R; Westwood, T; Wilbraham, L; Edwards, D W; Laasch, H U
Abstract : Introduction: A replacement button-gastrostomy has been developed, retained by a mechanical internal fixator formed by loops of the tube shaft. When stretched by the introducer/extractor tool it returns to a completely flat tube profile, avoiding the need for oversizing the stoma, reducing pain on exchange and potentially increasing the tube dwell time beyond the recommended 3 month intervals of balloon tubes. We assessed whether the prototype is applicable to clinical practice. Methods: Suitable patients referred for replacement of a conventional gastrostomy were invited to receive a 14Fr prototype instead of a 12Fr balloon gastrostomy requiring a 16Fr track. Gastrostomies were inserted without local anaesthesia, unless required for removal of the existing PEG/RIG. Regular follow-up at increasing periods was performed and difficulties and complications recorded. Informed consent and approval by the institutional review board was given, the device is CE marked. Results: All tubes were sited and subsequently exchanged without difficulty and essentially pain-free. Two patients had PEGs removed fluoroscopically under sedation prior to siting the tubes, 14 patients with an existing balloon tube found the exchange from much less painful. Initially the prototypes were changed routinely after 6 months. At present they are left until the patient indicates a need for review. No complications occurred during the insertion of the feeding tubes. No accidental displacements occurred. Seven feeding tubes (47%) are still in situ after a median of 250 days. Of the remaining tubes five were removed due to end of treatment, 4 were changed back to a balloon tube (two patient preference, two for infection and leakage). 14/16 patients indicated a clear preference for the prototype because of lack of balloon-maintenance, reduced number of tube changes and painfree tube removal and insertion. Conclusion: The feasibility study proved the mechanical retainer to have sufficient internal fixation with much reduced need for maintenance and applicable to clinical practice. Dwell time can easily exceed 1 year and patient acceptability was much higher than expected. The reduced number of tube changes and lack of pain of these would be particularly important in children. Competing interests: J Cain: None declared, T Westwood: None declared, L Wilbraham: None declared, D Edwards consultant for: Vygon, H U Laasch consultant for: Vygon, Kimberley-Clarke.